Anandamide transport inhibition by ARN272 attenuates nausea‐induced behaviour in rats, and vomiting in shrews (Suncus murinus). (15th October 2013) - O'Brien, L D; Limebeer, C L; Rock, E M; Bottegoni, G; Piomelli, D; Parker, L A
<x xml:space="preserve">Abstract</x> Background and Purpose To understand how anandamide transport inhibition impacts the regulation of nausea and vomiting and the receptor level mechanism of action involved. In light of recent characterization of an anandamide transporter, fatty acid amide hydrolase‐1‐like anandamide transporter, to provide behavioural support for anandamide cellular reuptake as a facilitated transport process. Experimental Approach The systemic administration of the anandamide transport inhibitor ARN272 ([(4‐(5‐(4‐hydroxy‐phenyl)‐3, 4‐diaza‐bicyclo[4.4.0]deca‐1(6), 2, 4, 7, 9‐pentaen‐2‐ylamino)‐phenyl)‐phenylamino‐methanone]) was used to evaluate the prevention of LiCl‐induced nausea‐induced behaviour (conditioned gaping) in rats, and LiCl‐induced emesis in shrews (Suncus murinus). The mechanism of how prolonging anandamide availability acts to regulate nausea in rats was explored by the antagonism of cannabinoid 1 (CB1) receptors with the systemic co‐administration of SR141716. Key Results The systemic administration of ARN272 produced a dose‐dependent suppression of nausea‐induced conditioned gaping in rats, and produced a dose‐dependent reduction of vomiting in shrews. The systemic co‐administration of SR141716 with ARN272 (at 3.0 mg·kg−1) in rats produced a complete reversal of ARN272‐suppressed gaping at 1.0 mg·kg−1. SR141716 alone did not differ from the vehicle solution. Conclusions and Implications These results suggest that anandamide transport inhibition by the compound ARN272 tonically activates CB1 receptors and as such produces a type of indirect agonism to regulate toxin‐induced nausea and vomiting. The results also provide behavioural evidence in support of a facilitated transport mechanism used in the cellular reuptake of anandamide.